Gingerol Inhibits Serum-Induced Vascular Smooth Muscle Cell Proliferation and Injury-Induced Neointimal Hyperplasia by Suppressing p38 MAPK Activation. (March 2016) - Jain, Manish; Singh, Ankita; Singh, Vishal; Maurya, Preeti; Barthwal, Manoj Kumar
Purpose: Gingerol inhibits growth of cancerous cells; however, its role in vascular smooth muscle cell (VSMC) proliferation is not known. The present study investigated the effect of gingerol on VSMC proliferation in cell culture and during neointima formation after balloon injury. Method and Results: Rat VSMCs or carotid arteries were harvested at 15 minutes, 30 minutes, 1, 6, 12, and 24 hours of fetal bovine serum (FBS; 10%) stimulation or balloon injury, respectively. Gingerol prevented FBS (10%)-induced proliferation of VSMCs in a dose-dependent manner (50 μmol/L-400 μmol/L). The FBS-induced proliferating cell nuclear antigen (PCNA) upregulation and p27 Kip1 downregulation were also attenuated in gingerol (200 μmol/L) pretreated cells. Fetal bovine serum-induced p38 mitogen-activated protein kinase (MAPK) activation, PCNA upregulation, and p27 Kip1 downregulation were abrogated in gingerol (200 μmol/L) and p38 MAPK inhibitor (SB203580, 10 μmol/L) pretreated cells. Balloon injury induced time-dependent p38 MAPK activation in the carotid artery. Pretreatment with gingerol (200 μmol/L) significantly attenuated injury-induced p38 MAPK activation, PCNA upregulation, and p27 Kip1 downregulation. After 14 days of balloon injury, intimal thickening, neointimal proliferation, and endothelial dysfunction were significantly prevented in gingerol pretreated arteries. In isolated organ bath studies, gingerol (30 nmol/L-300 μmol/L) inhibited phenylephrine-induced contractions and induced dose-dependent relaxation of rat thoracic aortic rings in a partially endothelium-dependent manner. Conclusion: Gingerol prevented FBS-induced VSMC proliferation and balloon injury-induced neointima formation by regulating p38 MAPK. Vasodilator effect of gingerol observed in the thoracic aorta was partially endothelium dependent. Gingerol is thus proposed as an attractive agent for modulating VSMC proliferation, vascular reactivity, and progression of vascular proliferative diseases.